Projeto arborizar Santarém: Arborização da Rodovia Fernando Guilhon - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
The development of cities, although seen as progress, imposes significant socio-environmental challenges, negatively impacting urban quality of life. Additionally, the removal of vegetation and uncontrolled construction have adverse effects on human health, such as pollution and thermal stress. Population growth also places pressure on green areas, reducing biodiversity and fragmenting ecosystems. In this context, the present study aimed to evaluate the implementation of the "Arborizar Santarém" Project on the Fernando Guilhon Highway. The project was carried out on one of the main highways in the city of Santarém, Pará, a municipality with a humid equatorial climate. Field research, conducted between June and August 2024, focused on planting 188 seedlings along Avenida Engenheiro Fernando Guilhon. The planted species included Pink Trumpet Tree (Handroanthus heptaphyllus), Yellow Trumpet Tree (Handroanthus albus), Oiti (Licania tomentosa), and Neem (Azadirachta indica). The seedlings were photographed, and their development was assessed through a structured questionnaire sent to the Municipal Environmental Secretariat (SEMAS). Despite the well-planned planting and favorable climatic conditions, the lack of maintenance and monitoring compromises the seedlings’ long-term success. Regular care, such as pruning and pest control, is crucial in the early years of tree development. The absence of monitoring prevents the early identification of problems, and the lack of an adequate soil study is a concerning factor that may negatively influence tree growth. Signage in the planting beds plays an educational role, raising public awareness about the importance of preserving urban greenery. However, the introduction of the exotic Neem species requires attention due to its invasive potential, which could impact local biodiversity. Therefore, the preservation and success of the project depend on continuous monitoring, maintenance, and environmental education for the population.
Keywords: Arborização urbana; Biodiversidade; Impacto ambiental; Preservação ambiental; CNPQ:: CIÊNCIAS SOCIAIS APLICADAS